Exploring the role of Digital Twin for Asset Lifecycle Management - Macchi, Marco; Roda, Irene; Negri, Elisa; Fumagalli, Luca (IFAC-PapersOnLine, 2018)
This work is an explorative study to reflect on the role of digital twins to support decisionmaking in asset lifecycle management. The study remarks the current convergence of needs for decision support from Asset Management and of potentials for decision support offered by Digital Twin modeling. The importance of digital twins is evident through state of the art as well as practical use case analysis.